2020
DOI: 10.1523/eneuro.0176-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β Impairs KIF1A Transport in a Cellular Model of Alzheimer’s Disease but Does Not Regulate Motor Motility at S402

Abstract: Impairment of axonal transport is an early pathologic event that precedes neurotoxicity in Alzheimer’s disease (AD). Soluble amyloid-β oligomers (AβOs), a causative agent of AD, activate intracellular signaling cascades that trigger phosphorylation of many target proteins, including tau, resulting in microtubule destabilization and transport impairment. Here, we investigated how KIF1A, a kinesin-3 family motor protein required for the transport of neurotrophic factors, is impaired in mouse hippocampal neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…In particular, under basal conditions, pGOLTtransfected neurons were characterized by an equal fraction of static, retrograde, and anterograde pGOLT vesicles, distributed along the entire dendritic tree. Short incubation with Aβ oligomers had a strong effect on vesicle trafficking, supporting the known effects of Aβ on molecular motors (Vicario-Orri et al, 2015;Gan and Silverman, 2016;Gan et al, 2020). In fact, we observed a significant reduction in the number of pGOLT vesicles as well as significant impairment in their mobility in both directions with respect to the control in all compartments analyzed.…”
Section: Effect Of Aβ and Mirtazapine On Golgi Vesicle Traffickingsupporting
confidence: 84%
See 1 more Smart Citation
“…In particular, under basal conditions, pGOLTtransfected neurons were characterized by an equal fraction of static, retrograde, and anterograde pGOLT vesicles, distributed along the entire dendritic tree. Short incubation with Aβ oligomers had a strong effect on vesicle trafficking, supporting the known effects of Aβ on molecular motors (Vicario-Orri et al, 2015;Gan and Silverman, 2016;Gan et al, 2020). In fact, we observed a significant reduction in the number of pGOLT vesicles as well as significant impairment in their mobility in both directions with respect to the control in all compartments analyzed.…”
Section: Effect Of Aβ and Mirtazapine On Golgi Vesicle Traffickingsupporting
confidence: 84%
“…Multiple mechanisms are involved in causing Aβ-induced neurodegeneration ( Resende et al, 2007 ). Among others, Aβ oligomers affect the structure and function of molecular motors required for neurite elongation, trafficking, and sorting of vesicles essential for synaptic function ( Brady and Morfini, 2017 ; Gan et al, 2020 ). In particular, Aβ induces Tau hyperphosphorylation and disengagement from microtubules affecting cargo transport, inducing deficits of neuronal protein transport, further leading to disruption of neuronal polarity ( Ballatore et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complex intramolecular interactions involving the motor domain, neck-coil, the coiled-coil stalk and the FHA domain inactivate the Kinesin-3-family motor (Al-Bassam et al, 2003;Lee et al, 2004;Ren et al, 2018;Siddiqui et al, 2019). A recent study further showed that the Aβ-induced activation of GSK3β could attenuate Kif1A transport in neurites of the mouse hippocampal neurons (Gan et al, 2020). Although GSK3β phosphorylated S402 of rat Kif1A in vitro, it did not appear to alter the motility of an autoinhibition-deficient KIF1A, suggesting that phosphorylation of additional components may be involved in this process.…”
Section: Phosphoregulation Of Kinesin-3mentioning
confidence: 99%
“…Interestingly, APLNR and SLC14A1 have also been found to be upregulated in AD [43][44][45][46] . The function of KIF1A has been shown to be impaired in the presence of Aβ oligomers 47 . While the repression of TAGLN3 has been recently reported to be attributed to APOE4 driven in ammation 48 and MTRNR2L6 peptides have been identi ed as neuroprotective species against Aβ toxicity in neurons and other cell types 49,50 .…”
Section: Discussionmentioning
confidence: 99%